SAT0250 Screening for Subclinical Pulmonary Vascular Disease of Systemic Sclerosis: The Best Non-Invasive Test and What We Found by Gene Expression Analysis of Peripheral Blood. (15th July 2016) - Koyama, Y.; Fuke, S.; Sato, Y.; Higuchi, T.
Abstract : Background: Pulmonary arterial hypertension (PAH) remains a leading cause of death in systemic sclerosis (SSc) in spite of current best treatments. As the better treatment effects is expected in the earlier PAH, current studies focus on early diagnosis. On the other hand, it is known that pulmonary vascular disease (PVD) can be well compensated for. Therefore, more than a half of the pulmonary circulation is considered to be obstructed by PVD before early PAH is detected. Recently, it has been reported that stress testing with exercise or infusion of dobutamine can reveal abnormal mean pulmonary artery pressure-cardiac output (mPpa-Q) responses, which may facilitate early diagnosis of PVD. Objectives: We tried to detect changes at the stage of subclinical PVD in SSc with using non-invasive or invasive examinations including pulmonary function test, cold stress thermography, stress Doppler echocardiography (DE) or stress right heart catheterization (RHC). And then, gene expression profiles, including subclinical PVD of SSc, in peripheral blood were explored Methods: Total of 58 cases categorized NYHA I with Raynaud symptoms (78.0%), puffy fingers (49.2%), or serological abnormality related to SSc including anti-centromere (44.8%), anti-topoisomerase I (1.7%), or anti-U1-RNP antibody positive (10.3%) were investigated. To find the best non-invasive index to screen for early PVD, correlation between mPpa-Q by dobutamine stress RHC and the result of clinical tests were evaluated (n=15). The tests includes serum BNP, %DLCO and %VC/%DLCO by pulmonary function test, thermography of hand with cold stress, resting tricuspid regurgitation pressure gradient (rest TRPG), maximum TRPG and mPpa-Q estimated by DE with Master's two-step stress. Then, the expressed genes in peripheral blood, which correlated with the best non-invasive index, were explored with using next-generation sequencing (n=58). Results: The mPpa-Q by dobutamine stress RHC was found to correlate most strongly with maximum TRPG estimated by exercise DE (R=0.65, p<0.01, FDR<0.05). The analysis of gene expression profile revealed that expressions of 94 genes were highly correlated with maximum TRPG by exercise DE (p<0.0001, FDR<0.05). It includes fibroblast growth factor (FGF) 12 (R=0.59, P<0.000001, FDR<0.05) and FGF 23 (R=0.50, P<0.0001, FDR<0.05). It also contained the genes of bone morphogenetic protein (BMP) 10 (R=0.47, P<0.001, FDR<0.05) and endothelin 2 (R=0.47, P<0.001, FDR<0.05), that are reported to be directly implicated in the development of PAH 1) . Conclusions: Although detection of early PVD in SSc patients remains a major challenge, maximum TRPG by stress DE seems to be an encouraging candidate for non-invasive screening. The results of gene expression analysis shed on changes in circulating blood cells at the early stage of SSc-associated PVD. By the analysis of gene expression, we found a very strong correlation between FGF12/23 and maximum TRPG by exercise DE. It is of particular interest that BMP-10 and endothelin-2 were also correlated significantly. As these factors were reported to be involved in the development of PAH, it is possible that theses factors could be candidates for therapeutic target to prevent the progression of SSc-associated PVD. References: Parikh VN et al., Circulation. 2012;125:1520–1532. Disclosure of Interest: None declared